2021
DOI: 10.1038/s41598-021-83910-w
|View full text |Cite
|
Sign up to set email alerts
|

Pathologically phosphorylated tau at S396/404 (PHF-1) is accumulated inside of hippocampal synaptic mitochondria of aged Wild-type mice

Abstract: Brain aging is a natural process characterized by cognitive decline and memory loss. This impairment is related to mitochondrial dysfunction and has recently been linked to the accumulation of abnormal proteins in the hippocampus. Age-related mitochondrial dysfunction could be induced by modified forms of tau. Here, we demonstrated that phosphorylated tau at Ser 396/404 sites, epitope known as PHF-1, is increased in the hippocampus of aged mice at the same time that oxidative damage and mitochondrial dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 91 publications
6
40
0
Order By: Relevance
“…However, this is the first report, to our knowledge, of age-related changes in phosphorylation at these two sites in vulnerable regions of the primate brain. A recent publication demonstrated an age-related increase in PHF-1 in synaptic mitochondria of wild-type mice, suggesting this may be a common mechanism of age-related neuronal dysfunction ( Torres et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the first report, to our knowledge, of age-related changes in phosphorylation at these two sites in vulnerable regions of the primate brain. A recent publication demonstrated an age-related increase in PHF-1 in synaptic mitochondria of wild-type mice, suggesting this may be a common mechanism of age-related neuronal dysfunction ( Torres et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all pathological conditions mentioned previously involve, almost in part, dysfunction of hippocampal neurons attributable to mitochondrial defects [64,65]. For example, mitochondrial dysfunction is considered a hallmark of aging and could be considered one of the factors leading to neurodegeneration [4,22,66]. Studies in humans and animal models showed that decreased memory correlates with reduced cerebral energetics metabolism and more specifically to mitochondrial bioenergetics deficits [4,22,66].…”
Section: Rl-tclt Mechanisms: Improving Mitochondrial Functionmentioning
confidence: 99%
“…For example, mitochondrial dysfunction is considered a hallmark of aging and could be considered one of the factors leading to neurodegeneration [4,22,66]. Studies in humans and animal models showed that decreased memory correlates with reduced cerebral energetics metabolism and more specifically to mitochondrial bioenergetics deficits [4,22,66]. Therefore, the mitochondrial focus of aging and neurodegenerative diseases is of great interest for the development of a potent and ideally non-invasive anti-aging intervention to improve or attenuate cognitive impairment in the elderly.…”
Section: Rl-tclt Mechanisms: Improving Mitochondrial Functionmentioning
confidence: 99%
“…The hyperphosphorylation of tau causes most of the pathological synaptic features seen in AD by increasing the mislocalization of tau from the axonal compartment to the somatodendritic compartment, where it aggregates into oligomers [80,111]. Indeed, AD brains show decreased levels of protein phosphatase 2 (PP2A), a phosphatase implicated in the regulation of AMPARs in membrane.…”
Section: Pathogenic Tau In Synapsesmentioning
confidence: 99%